2016
DOI: 10.2106/jbjs.rvw.15.00102
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm for Diagnosing and Treating Primary and Recurrent Patellar Instability

Abstract: Major anatomic risk factors for recurrent patellar instability include trochlear dysplasia, patella alta, a lateralized tibial tuberosity, and medial patellofemoral ligament insufficiency. Acute first-time patellar dislocation may be treated nonoperatively in the absence of osteochondral injury. Recurrent patellar instability often requires medial patellofemoral ligament reconstruction, with osseous procedures reserved for patients with substantial underlying anatomic abnormalities. Surgical treatment of patel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 99 publications
0
41
0
6
Order By: Relevance
“…26 Current standard of care for the majority of patients without a significant osteochondral injury or loose body who sustain a first-time lateral patellar dislocation is nonoperative treatment focused on rest as well as patellar stabilization rehabilitation. 12,15,30 Success rates in nonoperative treatment of first-time patellar dislocations vary: a recent meta-analysis found a mean redislocation rate of 34.6% and recurrent instability of 32.8% among patients treated nonoperatively. Other studies identified a high-risk subset of patients \25 years old with trochlea dysplasia, with up to a 69% risk of recurrent dislocation at 5 years.…”
mentioning
confidence: 99%
“…26 Current standard of care for the majority of patients without a significant osteochondral injury or loose body who sustain a first-time lateral patellar dislocation is nonoperative treatment focused on rest as well as patellar stabilization rehabilitation. 12,15,30 Success rates in nonoperative treatment of first-time patellar dislocations vary: a recent meta-analysis found a mean redislocation rate of 34.6% and recurrent instability of 32.8% among patients treated nonoperatively. Other studies identified a high-risk subset of patients \25 years old with trochlea dysplasia, with up to a 69% risk of recurrent dislocation at 5 years.…”
mentioning
confidence: 99%
“…The optimal treatment algorithm for addressing lateral patellar instability needs to be further refined. 5,8,9 The biomechanical properties and function of the individual medial ligaments attaching to the patella must be determined to restore the native kinematics of the patella. In this regard, we were motivated to determine whether further quantification of the biomechanical properties of each individual ligament of the medial side of the patellofemoral joint would help to explain injury patterns and advance reconstruction techniques by improving the selection of appropriate grafts for each ligament.…”
mentioning
confidence: 99%
“…Previous studies have also introduced how to manage patients with patellar dislocation. 7 , 8 They either elaborated on this disease in all aspects or only in a particular risk factor. However, the overall process of patient evaluation and formulation of treatment plans have rarely been described in these kinds of review articles or original articles.…”
Section: Discussionmentioning
confidence: 99%